Industri Perunggasan: Memadukan Pertumbuhan dan Pemerataan (Forum Penelitian Agro Ekonomi, 2016)
EnglishRegarding sustainable economic development, the government have to consider three main roles, i.e. : to accelerate growth through efficiency improvement, to generate equity and justice, and to maintain stability as well as macro-economic growth. The economic system being exclusively bias to one of the said economic dimensions will not sustainable in the long-run. The assessment which accommodate complementary growth and equity on poultry industry is important, due to structural problems on the respective industry, in addition to marginalization of smallholder poultry farmers. Government policies being bias toward economic growth in the condition of economic crisis have substantial negative impact on national poultry industry. IndonesianDalam konteks pembangunan ekonomi berkelanjutan pemerintah mempunyai tiga fungsi sentral yaitu meningkatkan efisiensi guna mempercepat pertumbuhan, menciptakan pemerataan dan keadilan, memacu pertumbumhan ekonomi secara makro dan menjaga stabilitasnya. Suatu sistem perekonomian yang bias ke salah satu tujuan akan menghasilkan kinerja pembangunan ekonomi yang rapuh. Dalam kontek ini, kajian yang memadukan antara pertumbuhan dan pemerataan pada industri perunggasan di pandang sangat relevan, karena pada bidang usaha ini telah terjadi ketimpangan struktur pasar input, pasar hasil (output), integrasi vertikal dan horisontal, dan tersisihnya peternakan rakyat. Kebijakan pemerintah yang bias ke pemacuan pertumbuhan ekonomi adanya dampak krisis ekonomi berkepanjangan telah berdampak buruk pada kinerja industri perunggasan